2005
DOI: 10.1007/s11095-004-1190-6
|View full text |Cite
|
Sign up to set email alerts
|

Altered Pharmacokinetics of Paclitaxel in Experimental Hepatic or Renal Failure

Abstract: These results suggested that not only hepatic failure but also renal failure could modify the pharmacokinetics of paclitaxel in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In the present study, CCl 4 treatment induced apparent liver dysfunction without renal damage, and glycerol treatment induced marked renal dysfunction with little liver injury. These results are mostly consistent with the previous studies [5,10]. Therefore, our results confirm that CCl4 and glycerol treatment induce selective hepatic and renal dysfunction.…”
Section: -Note-supporting
confidence: 93%
“…In the present study, CCl 4 treatment induced apparent liver dysfunction without renal damage, and glycerol treatment induced marked renal dysfunction with little liver injury. These results are mostly consistent with the previous studies [5,10]. Therefore, our results confirm that CCl4 and glycerol treatment induce selective hepatic and renal dysfunction.…”
Section: -Note-supporting
confidence: 93%
“…A formal preclinical toxicity study was not completed because it was only necessary to identify a safe dose in rats that could be used for subsequent studies to determine the bioavailability of paclitaxel following the oral administration of Taxol TM and other formulations. Relatively few studies have reported the pharmacokinetic parameters for paclitaxel following Taxol TM in rats [18,19]. About 100 studies identified using PubMed TM with the search terms: rats, pharmacokinetics and paclitaxel were examined; however, only two studies described the pharmacokinetics of Taxol TM following an intravenous bolus in rats [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In previous kinetic analyses of TST 6b-hydroxylation by rat liver microsomes, velocity data were fitted to a one-enzyme hyperbolic kinetic model (Jimenez et al, 1992;Murray and Butler, 1996;Jiko et al, 2005;Velenosi et al, 2012) or to a sigmoidal kinetics with low degree of autoactivation [Hill coefficients of 1.2-1.4 (Carr et al, 2006)]. This did b CL int is expressed as ml/min per mg protein for liver microsomes and ml/min per pmol P450 for recombinant enzymes.…”
Section: Discussionmentioning
confidence: 99%